Transcranial Doppler Ultrasound: Technique and Application - Purkayastha, Sushmita; Sorond, Farzaneh (Seminars in Neurology, 2012)
Transcranial Doppler (TCD) ultrasound provides rapid, noninvasive, real-time measures of cerebrovascular function. TCD can be used to measure flow velocity in the basal arteries of the brain to assess relative changes in flow, diagnose focal vascular stenosis, or to detect embolic signals within these arteries. TCD can also be used to assess the physiologic health of a particular vascular territory by measuring blood flow responses to changes in blood pressure (cerebral autoregulation), changes in end-tidal CO2 (cerebral vasoreactivity), or cognitive and motor activation (neurovascular coupling or functional hyperemia). TCD has established utility in the clinical diagnosis of a number of cerebrovascular disorders such as acute ischemic stroke, vasospasm, subarachnoid hemorrhage, sickle cell disease, as well as other conditions such as brain death. Clinical indication and research applications for this mode of imaging continue to expand. In this review, the authors summarize the basic principles and clinical utility of TCD and provide an overview of a few TCD research applications.
Keywords: transcranial Doppler; cerebral blood flow; ultrasound; cerebrovascular diseases